Developing Sustainability Governance Model for Smallholders in Palm Oil Industry through Engagement with Supply Chain Key Players - Ahmad, Adura; Ooi, Sue Chern; Chandren, Sitraselvi; Mohd Rashid, Rasidah; Amran, Azlan (Universiti Utara Malaysia, 2022)
Malaysian Sustainable Palm Oil (MSPO) is a national standard in Malaysia that promotes the long-term sustainability of the oil palm sector. It was announced in 2013, and the certification scheme's voluntary deployment began in 2015. With the mandatory deployment of MSPO, industries, especially smallholders, have emphasized their commitment to sustainability. In line, independent smallholders play an important role in the palm oil sector in Malaysia, contributing for more than 16 percent of total oil palm land area. For continuous sustainability this study has threefold research objectives. 1) to examine the practices of smallholders that contributes to sustainable palm oil production; 2) to investigate way in ensuring the inclusion of smallholders into the sustainable supply chain of palm oil; and 3) to develop a sustainability governance model as a best practice guide in sustainable production of palm oil for smallholders. This study included a combination of qualitative research methodologies, including semi-structured interviews and narrative analysis. In all, 22 in-depth semi-structured interviews with major actors such as rule enforcer, smallholders and buyers in the palm oil industry were conducted. As per the findings, smallholders credit the government assistance in the form of audit fee subsidies and free training programs to get accredited, but it is insufficient. Even with the MSPO certification, there is no difference in term of pricing and ability to sell the Fresh Fruit Bunches (FFB) to dealers and agents, as compared to those without certification. Thus, there was little evidence of their effectiveness in resolving social and environmental controversy. Nevertheless, the findings imply that smallholder sustainability practices are inextricably tied to arena discourses and engagement activities. This study contributes to the social and environmental accounting literature by examining how smallholders in palm oil industry construct sustainability practices.